Pythagoras and the early Pythagoreans - Žmudʹ, Leonid Jakovlevič 1956- (Oxford University Press, 2012)
In ancient tradition, Pythagoras emerges as a wise teacher, an outstanding mathematician, an influential politician, and as a religious and ethical reformer. This volume offers a study of Pythagoras, Pythagoreanism, and the early Pythagoreans through an analysis of the many representations of the individual and his followers
Includes bibliographical references and index
Keywords: Pythagoras -- ca. 6./5. Jh. v. Chr.; Pythagoras and Pythagorean school; Philosophie; Wissenschaft; Religion; Pythagoreer